FOPID Controller Based AC Pump Supplied from PV Standalone Source Tuned using Fuzzy Logic Type 2 - Mohamed Mahmoud Ismail; Ahmed Fahmy Bendary (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper presents 500 KW three phase standalone photovoltaic systems supplying pumping station consist of four pumps 80 KW rating. The system utilizes a two stage energy conversion power conditioning unit topology composed of a DC-DC boost converter and three level-three phase voltage source inverter (VSI). The Boost converter in this paper is designed to operate in continuous mode and controlled for maximum power point tracking (MPPT). In this paper, the performance of the pumps is improved by adapting the controller of MPPT using different techniques. The system is modeled and studied using MATLAB/Simulink.